To BlikBook or not to BlikBook: Exploring student engagement of an online discussion platform. Issue 3 (4th May 2019) - Crowder, Mark; Antoniadou, Marilena; Stewart, Jim
ABSTRACT: This paper reports on the use of BlikBook, a course engagement platform for tutors and students that facilitates academic engagement in higher education. Based on a case study where BlikBook was essential to the design and delivery of a large undergraduate module, the paper discusses how the platform opens new avenues for student feedback, and encourages more independence in peer-led student groups. The paper makes several important contributions to knowledge and practice. Firstly, it outlines the process of introducing new software within a university context, and identifies potential pitfalls. Secondly, it offers an assessment of BlikBook that was previously untried in the case study organisation. Thirdly, previous studies have focused primarily on students' perceptions of online platforms, rather than on the differences in experiences between students and tutors, whereas the present study explores both aspects. Findings suggest that incorporating BlikBook in teaching could improve student engagement. Abbreviation: (HE) - Higher Education